2005 IEEE International Conference on Multimedia and Expo
DOI: 10.1109/icme.2005.1521448
|View full text |Cite
|
Sign up to set email alerts
|

A Quarter Pel Full Search Block Motion Estimation Architecture for H. 264/AVC

Abstract: This paper presents a novel quarter pel full search block motion estimation architecture for H.264/AVC encoder. The proposed architecture is capable of calculating all 41 motion vectors required by the various size blocks, supported by H.264/AVC, in parallel. The architecture has been prototyped in Verilog HDL, simulated and synthesized for Xilinx Virtex2 FPGA. The experimental result shows that the architecture is capable of processing CIF frame sequences in real time considering 5 reference frames within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…Performance of the proposed architecture has been compared with other existing architectures [19,[22][23][24][25]. It is found that proposed architecture has several advantages over other existing architectures (see Table 2).…”
Section: Hardware Comparisonmentioning
confidence: 98%
See 1 more Smart Citation
“…Performance of the proposed architecture has been compared with other existing architectures [19,[22][23][24][25]. It is found that proposed architecture has several advantages over other existing architectures (see Table 2).…”
Section: Hardware Comparisonmentioning
confidence: 98%
“…To solve the memory bandwidth limitation, several techniques have been developed, e.g., (1) caching, (2) memory interleaving, (3) parallel memory banks, (4) pipelining, and (5) hierarchical memory [19]. In this paper, to efficiently reduce memory access conflicts and reuse data, a multiport memory network architecture is used, in which there are four banks to buffer the search window (SW) data, current block (CB) data and MVs.…”
Section: Memory Networkmentioning
confidence: 99%
“…The architecture described in [21] reduces the search area and number of MVs needed in order to achieve low-latency and hardware efficiency. Finally, designs suitable for a FPGA implementation are presented in [22,23] In this paper, a VLSI architecture based on the full-search algorithm for implementation of FME is described. Its architecture is made up of three different pipeline processors: a half-pixel processor, a quarter-pixel processor and a mode decision processor.…”
Section: Introductionmentioning
confidence: 99%
“…Although VBS-BMA achieves higher coding performance than that of FBS-BMA, it requires a high computation effort since 41 motion vectors of 7 different sizes should be computed for each macroblock. Therefore, many efficient hardware architectures such as systolic array [8], 1-D processing element (PE) array [6] and 2-D PE array [4] [7] [10] have been proposed for implementing VBS-BMA. The 1-D PE array is a simple structure, as it is easier to control and less gates than a 2-D PE array, but it is normal to search the sum of absolute difference (SAD) against only one row or a column of the macroblock at a time.…”
Section: Introductionmentioning
confidence: 99%